A multidisciplinary weight management intervention for adults with severe mental illness in forensic psychiatric inpatient services (Motiv8): a single blind cluster-randomised wait-list controlled feasibility trial - Carney, Rebekah; Law, Heather; El-Metaal, Hany; Hann, Mark; Shields, Gemma; Savage, Siobhan; Small, Ingrid; Jones, Richard; Shiers, David; Macafee, Gillian; Parker, Sophie (Frontiers in Psychiatry, 2024)
BackgroundPeople with severe mental illness experience physical health inequalities and a 15–20-year premature mortality rate. Forensic inpatients are particularly affected by restrictions on movement, long admissions, and obesogenic/sedative psychotropic medication. We aimed to establish the feasibility and acceptability of Motiv8, a multidisciplinary weight management intervention co-produced with service users for forensic inpatients.MethodsA randomised waitlist-controlled trial of Motiv8(+Treatment-As-Usual) vs.TAU was conducted in medium-secure forensic services in Greater Manchester. Motiv8 is a 9-week programme of exercise sessions, diet/cooking classes, psychology, physical health/sleep education, and peer support. Physical and mental health assessments were conducted at baseline/10-weeks/3-months. A nested qualitative study captured participant experiences. A staff sub-study explored ward environment.ResultsWe aimed to recruit 32 participants (four cohorts). The trial met recruitment targets (n=29, 90.9%; 4 cohorts, 100%), participants were randomised to Motiv8+TAU (n=12) or waitlist (control) (n=17). Acceptable retention rates were observed (93.1%, 10-weeks; 72.4%, 3-months), and participants engaged well with the intervention. The blind was maintained, and no safety concerns raised. Assessment completion was high suggesting acceptability (>90% for people retained and engaged in the study). Participants reported high levels of satisfaction.ConclusionsThe trial was not powered to detect group differences. However, data suggests it is feasible to conduct a rigorous, methodologically robust study of Motiv8 vs.TAU for adults on forensic inpatient units. Motiv8 was acceptable with potential promise providing evidence to proceed to a definitive trial for males. A larger trial is needed to explore potential effectiveness and reduce physical health inequalities for people with SMI.Clinical trial registrationhttps://doi.org/10.1186/ISRCTN13539285, identifier ISRCTN13539285.